Type 2 diabetes, thiazolidinediones, and cardiovascular risk. - Taylor, C; Hobbs, F (2009)
Type 2 diabetes is a common disorder with an increased risk of macrovascular complications. Achieving adequate glycaemic control is an important aim of therapy. Thiazolidinediones, or glitazones, have been used for the treatment of diabetes for a decade. Rosiglitazone and pioglitazone are currently available, however recent concerns around cardiovascular safety have led to restrictions on their use. Initial trials showed treatments with glitazones improved glycaemic control, however long-term outcomes such as cardiovascular events were not measured. Evidence from more recent trials suggests rosiglitazone is associated with an increased risk of cardiovascular events and both glitazones are associated with higher rates of heart failure. This article discusses the evidence behind these concerns and the most recent guidance on use of thiazolidinediones in clinical practice.